For the creation of character: Pedagogical approach in Ontario's character development education resources - Pyykonen, Amanda (University of Ottawa (Canada), 2008)
This thesis addresses Ontario's current state of transition into mandated character development education that began with the onset of the Character Development Initiative at the beginning of the 2007/2008 school-year. The history of moral and character development educational efforts in Ontario, and in the broader North American context, is presented with specific attention paid to the development of pedagogies for character development and moral growth. By examining the pedagogical approaches suggested in three readily available resources published in the recent past and in use by teachers in Ontario data on what kinds of pedagogical approaches pre-date the Initiative was gathered. Data was collected from the introductions of each resource initially in order to establish the suggested or intended pedagogical approach by assessing statements of philosophical positioning. This was followed by a careful reading of the activities presented in the resource for teacher directives. The concept of pedagogical continuity was central to the analysis of these documents, and this extended to consistency of the resource's treatment of critical engagement. Commonalities were observed in the techniques and strategies suggested in the resources, especially where cooperative education is concerned. The common use of cooperative education in the documents was observed with a high level of internal continuity in the documents, and external continuity with the expectations of the Character Development Initiative was also seen. Levels of critical engagement in the resources varied, yet no document singled out that characteristic as being of high importance. This research adds to the knowledge base on pedagogy in the Ontario context as it relates to character development and opens the door for further studies of this nature.
Keywords: Education, Curriculum and Instruction.